Feminicide: Reality or Myth in Colombian Public Policy - Correa Corredor, Marien Yolanda; Mendoza Pérez, Noris; Rincón Guauque, Clara Milena; Arenas Rueda, Yenny Marcela; Aguilar Noriega, Erick Johann; Villamizar Mendoza, José Eliecer (DIXI, 2014)
This academic exercise is based on the state of the art on feminicide in six Latin American countries, including Colombia, over the past two decades to show the need to propose a defiition of feminicide, not as an aggravating aspect of homicide but as a separate offnse under Colombian law. It was written based on the theory of feminicide of Diana Marcela Russell and Lagard, in line with public policy to protect women victims and was the result of two completed research papers. Th conclusion is that a large part of public policy supports a decrease in violence against women and also serves to modify collective concepts.
Keywords: feminicide; misogyny; killing women; women; gender violence